Principal Management and Its Impact on Teacher Performance in Elementary School Learning: Systematic Literature Review - Wulaningrum, Liring Puspita; Muhimmah, Hitta Alfi; Hariyati, Nunuk (Papanda Publisher, 2025)
The leadership of school principals has a strategic role in improving teacher effectiveness, learning quality, and job satisfaction of educators. This study aims to systematically analyze the role of school principals in improving teacher effectiveness, learning quality, and job satisfaction of educators by conducting a Systematic Literature Review (SLR) of peer-reviewed journal articles published between 2021 and 2025. The methods used include identification, selection, analysis, and synthesis of relevant articles from various indexed journals. A total of 15 articles were selected from databases including Scopus, ERIC, and Google Scholar, using inclusion criteria such as publication year (2021–2025), focus on elementary education, and discussions on leadership models. Exclusion criteria included studies not focused on teacher performance or non-elementary levels. A total of 15 articles that discuss the leadership of school principals, both in instructional, transformational, and distributional contexts, were studied in depth. The results of the analysis showed that instructional and transformational leadership styles consistently demonstrated a positive impact on teacher motivation, job satisfaction, and instructional effectiveness, while transactional leadership often correlated with decreased teacher engagement and performance. In addition, supporting factors such as the work environment, teacher training, and strategic management of school principals contribute to improving the quality of education. However, challenges such as high workloads and stress in school leadership require more systematic solutions. Quantitatively, over 70% of the reviewed studies emphasized the importance of adaptive leadership approaches in overcoming teacher-related challenges. Thus, it is necessary to develop policies and leadership strategies that are more innovative, adaptive, and oriented towards the welfare of teachers to create a more quality and sustainable education system.